PENGARUH KINERJA KEUANGAN KABUPATEN/ KOTA TERHADAP ALOKASI BELANJA MODAL DI PROVINSI SULAWESI UTARA - Gerungan, Sylvia Febriany; Saerang, David Paul Elia; Pontoh, Winston (Universitas Sam Ratulangi, 2015)
The regional autonomy policy gives more chance to local goverment for managing their own financial. To determine the success of local goverment in managing their own financial, Financial Performance Analysis can be used. The objective of this research is to determine the influence of regional financial performance toward the capital expenditure allocation in forward years of regency/city of North Sulawesi. The data analysis method used in this research is regression. The results show that, simultaneously, the Regional Financial Independence ratio, Regional Financial Dependence ratio, Local Original Revenue Effectiveness ratio, Capital Expenditure Effectiveness ratio, Efficiency ratio, and Expenditure Harmony ratio significantly effect the Capital Expenditure Allocation. Partially, the Regional Financial Independence ratio and Efficiency ratio, significantly, have a negative effect toward the Capital Expenditure Allocation. While, the Local Original Revenue Effectiveness ratio and Expenditure Harmony ratio have a positive effect toward the Capital Expenditure Allocation. The Regional Financial Dependence ratio and Capital Expenditure Effectiveness have no significant effect toward the Capital Expenditure Allocation.